Assessment of low-rise reinforced concrete building in low seismicity region - Fateha Shahrin (School of Environmental Engineering, University Malaysia Perlis, 2012)
A literature review has been conducted aimed at improving the general understanding of the seismic response of concrete buildings in low-to-moderate seismicity regions. This paper summarizes and discusses the existing codified requirements for transfer structure design under seismic conditions. Damage and collapse occurred due to seismic action can be observed to reinforced concrete buildings designed by considering gravity load only. The damage will be prominent because the irregularity in plan. Based on this project, we present the seismic performance of three-story reinforced concrete building as the modeled and designed the building by regular and irregular building. These modeled showed us the different of the design concrete structure and analysis for the two types of buildings. The performance of two commonly used spectral forms along with a newly proposed one is assessed with respect to the elastic displacement design spectrum defined by the European code regulations (EC8). The ductility demand and overstrength of buildings were determined by do the push over analysis using SAP2000. The capacity curve will obtain in the end of result; than the buildings will be compare using two models regular and irregular building.The aims of this study are to investigate the ductility demand and overstrength of reinforced concrete building in low seismicity region. Low rise RC building with regular and irregular in elevation are considered in this study. These frame models are designed to gravity and earthquake load according to EC2 and EC8. Pushes over analysis (POA) are used to analyze the frames. The global ductility demand and overstrength factor for irregular and regular in elevation frames show significant different.